Information percolation and cutoff for the random‐cluster model. Issue 3 (5th June 2020) - Ganguly, Shirshendu; Seo, Insuk
Abstract : We consider the random‐cluster model (RCM) on ( Z / n Z ) d with parameters p ∈(0, 1) and q  ≥ 1. This is a generalization of the standard bond percolation (with edges open independently with probability p ) which is biased by a factor q raised to the number of connected components. We study the well‐known Fortuin‐Kasteleyn (FK)‐dynamics on this model where the update at an edge depends on the global geometry of the system unlike the Glauber heat‐bath dynamics for spin systems, and prove that for all small enough p (depending on the dimension) and any q >1, the FK‐dynamics exhibits the cutoff phenomenon at λ ∞ − 1 log n with a window size O ( log log n ), where λ ∞ is the large n limit of the spectral gap of the process. Our proof extends the information percolation framework of Lubetzky and Sly to the RCM and also relies on the arguments of Blanca and Sinclair who proved a sharp O ( log n ) mixing time bound for the planar version. A key aspect of our proof is the analysis of the effect of a sequence of dependent (across time) Bernoulli percolations extracted from the graphical construction of the dynamics, on how information propagates.